God and gods in the deuteronomistic history - Carvalho, Corrine L.; McLaughlin, John L. (Catholic Biblical quarterly imprints ;, 2021)
"God and Gods in the Deuteronomistic History stems from a four-year seminar at the Catholic Biblical Association Annual International Meetings. The essays examine topics related to divinity in each of the historical books (Joshua, Judges, 1 and 2 Samuel, and 1 and 2 Kings), such as cultic representation, divine characteristics, the relevance of redactional layers, and the role of religion in Israel's telling of its history."--